Highly anisotropic Zeeman splittings of wurtzite Cd[sub 1−x]Mn[sub x]Se quantum dots - Li, Shu-Shen. (2013)
The electronic structure and Zeeman splittings of wurtzite Cd1−xMnxSe quantum spheres are studied using the k· p method and mean-field model. It is interesting to find that the Zeeman splittings of some hole states in quantum spheres are highly anisotropic due to the spin-orbit coupling and wurtzite crystal structure. The anisotropy of the Zeeman splittings of hole ground states in large dots is large, while that in small dot is small because the hole ground states vary with radius. An external electrical field can change the Zeeman splitting significantly, and tune the g factor from nearly 0 to about 100.